Genome-wide association mapping and gene expression analysis reveal candidate genes for grain chalkiness in rice - Huo, Xing; Wang, Jian; Chen, Luo; Fu, Hua; Yang, Tifeng; Dong, Jingfang; Ma, Yamei; Zhou, Lian; Chen, Jiansong; Liu, Dilin; Liu, Bin; Zhao, Junliang; et al. (Frontiers in Plant Science, 2023)
Grain chalkiness is the main factor determining the market value of rice. Reducing chalkiness is an important breeding goal for genetic improvement of high quality rice. Identification of QTLs or genes controlling chalkiness is the prerequisite for molecular breeding in rice. Here, we conducted a genome-wide association study to identify QTLs associated with grain chalkiness including percentage of grains with chalkiness (PGWC) and degree of endosperm chalkiness (DEC) in 450 rice accessions consisting of 300 indica and 150 japonica rice in two environments. A total of 34 QTLs were identified, including 14 QTLs for PGWC and 20 QTLs for DEC. Among them, seven QTLs were commonly identified in two environments, and eight QTLs were simultaneously related to two traits. Based on the haplotype analysis, LD decay analysis, RNA-sequencing, qRT-PCR confirmation and haplotype comparisons, four genes (LOC_Os10g36170, LOC_Os10g36260, LOC_Os10g36340 and LOC_Os10g36610) were considered as the candidate genes for qDEC-10c1w,2wj, which could be identified in both environments and had the most significant p-value among the newly identified QTLs. These results provided new insight into the genetic basis of grain chalkiness and gene resources for improving quality by molecular breeding in rice.